Darkness, Silence and Emptiness - Rojas G., Margarita (2016)
A general interpretation is proposed of Los detectives salvajes, by Roberto Bolaño, beginning with the analysis of its structure. Other aspects studied include games, the opposition between loyalty and betrayal, and verosimilitude based on repetitions in the interviews. Mention is also made of other works by Roberto Bolaño, such as Amuleto, Estrella distante y 2666.